2020
DOI: 10.3390/metabo11010001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis to Elucidate Mechanisms of Sunitinib Resistance in Renal Cell Carcinoma

Abstract: Metabolomics analysis possibly identifies new therapeutic targets in treatment resistance by measuring changes in metabolites accompanying cancer progression. We previously conducted a global metabolomics (G-Met) study of renal cell carcinoma (RCC) and identified metabolites that may be involved in sunitinib resistance in RCC. Here, we aimed to elucidate possible mechanisms of sunitinib resistance in RCC through intracellular metabolites. We established sunitinib-resistant and control RCC cell lines from tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 47 publications
(68 reference statements)
3
30
0
Order By: Relevance
“…( Z )-sunitinib ( Figure 4 A, 2) is clinically relevant and active. The two stereoisomers could be detected at the same ratios in the supernatant, independent of the dose of sunitinib, with the percent of stereoisomeric excess (see Materials and Methods) being approximatively 85% ( Z/E ) at all concentrations ( Supplementary Figure S8B ), which is slightly lower than the values reported in the literature [ 31 , 33 ]. The increasing percentage of stereoisomeric excess at low concentrations can be attributed to the limit of detection of peak 1 (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…( Z )-sunitinib ( Figure 4 A, 2) is clinically relevant and active. The two stereoisomers could be detected at the same ratios in the supernatant, independent of the dose of sunitinib, with the percent of stereoisomeric excess (see Materials and Methods) being approximatively 85% ( Z/E ) at all concentrations ( Supplementary Figure S8B ), which is slightly lower than the values reported in the literature [ 31 , 33 ]. The increasing percentage of stereoisomeric excess at low concentrations can be attributed to the limit of detection of peak 1 (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 61%
“…Investigation of the conversion of sunitinib in Caki-1-SR cells through LC-HRMS/MS was performed and showed two peaks corresponding to its ( E ) and ( Z )-isomer ( m/z = 399.2183; Figure 4 A and Supplementary Figure S8A ). Diverse studies showed the presence of both stereoisomers, ( E )-sunitinib and ( Z )-sunitinib [ 23 , 31 , 33 ]. Attribution was made by comparing the retention times and stereoisomeric ratios with the literature [ 32 ] and a standard solution in methanol ( Supplementary Figure S8A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations